Metáforas literarias: El escenario ’intertextual’ en La virgen triste y Beijo - Hodge, Polly J. (Latin American Theatre Review, 2002)
This project is an investigation of the theoretical ramifications involved with the concept of literary intertextuality as concerns the study of theatre. My thesis is that the literary intertexts serve as springboards for the expression of "socio-literary" metaphors in the unfolding of the production in theatre, i.e. metaphors pertinent to the context of the cultural sphere where the play was produced. The practical basis of this study lies in the analysis of two plays which encompass literary intertexts: La Virgen Triste (Elizabeth Mena), a Cuban play, and Beijo (Tuca Pinheiro and Suely Machado) a dance-theater production from Brazil. This investigation reveals the intense intermingling of theatre, literature and society (PJH, in Spanish).